2015
DOI: 10.1007/s10530-015-0884-5
|View full text |Cite
|
Sign up to set email alerts
|

Improving science-based invasive species management with physiological knowledge, concepts, and tools

Abstract: Biological invasions are a prominent factor contributing to global biodiversity loss. As a result, managing invasive species is a priority for many conservation scientists and natural resource managers. Invasive species management requires a multidisciplinary approach and there is increasing recognition that physiology can be used to inform conservation efforts because physiological processes underlie an individual's response to its environment. For example, physiological concepts and tools can be used to asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
41
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 106 publications
1
41
0
Order By: Relevance
“…Besides refining current tolerance classifications (e.g. Bonada et al, 2004;Maceda-Veiga and de Sostoa, 2011), these studies could help identify species according to their vulnerability to stressors and/ or invasive traits (Gallagher et al, 2015;Lennox et al, 2015). For example, Faria et al (2010b) found that transplanted native naiads were less vulnerable to mercury pollution than two exotic freshwater bivalve species (D. polymorpha and Corbicula fluminea).…”
Section: Macro-invertebrates and Fish As Bio-indicator Speciesmentioning
confidence: 99%
“…Besides refining current tolerance classifications (e.g. Bonada et al, 2004;Maceda-Veiga and de Sostoa, 2011), these studies could help identify species according to their vulnerability to stressors and/ or invasive traits (Gallagher et al, 2015;Lennox et al, 2015). For example, Faria et al (2010b) found that transplanted native naiads were less vulnerable to mercury pollution than two exotic freshwater bivalve species (D. polymorpha and Corbicula fluminea).…”
Section: Macro-invertebrates and Fish As Bio-indicator Speciesmentioning
confidence: 99%
“…We sought to identify novel approaches to the analysis of invasive species’ evolutionary adaptation, range expansion, and ecological impacts through the explicit recognition of a fundamental link between an organism's physiology and its environment and how this relationship varies through space and time (Chown , Lennox et al. ). Ultimately, by continuing to work with the participants post‐workshop, our goal is to advance a coherent physiological ecology theory that can integrate across biological, spatial, and temporal scales of invasions to inform future research approaches.…”
mentioning
confidence: 99%
“…Although these insights have previously received some attention in invasion science (Lennox et al. ), they have not yet coalesced into a coherent research agenda within the field. The allied approach of conservation physiology (Cooke et al.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Phenotypic variation in dispersal-related traits is strongly associated with the range expansion of invasive species (Chuang & Peterson 2016), therefore understanding contemporary evolution dynamics of morphological, physiological, and behavioural traits is crucial for effective distribution modelling (Travis & Dytham 2002;Bocedi & Travis 2016) and invasive species management (Lennox et al 2015). Many invasive species (including amphibians, birds, fish, and insects) have been found to exhibit certain traits that assist in their dispersal ability, and rapid phenotypic change occurs at expanding range edges (Llewelyn et al 2010;Berthouly-Salazar et al 2012;Laparie et al 2013;Myles-Gonzalez et al 2015;Davenport & Lowe 2016).…”
Section: Evolution Of Dispersalmentioning
confidence: 99%